Brain Experience: Neuro experimential persectives of brain mind - C R Mukundan (Atlantic Publishers & Distributors, 2007)
The present book deals with the brain-mind, based on the findings of studies using functional neuroimaging, cognitive electrophysiological and clinical neuropsychological techniques. The meta-analysis draws on the emergence of the mind from the brain and the control of mental activities by the neural systems. Nevertheless, interpretations that determine the contents of processing and their qualitative judgements are not limited by the brain or the realities of the world. It is possible to create a subjective world, which is not in conformity with objective realities. The environment controls the brain and the brain has learnt to internalize such controls and selectively use them for dealing with various environmental exigencies. The human brain has further learnt to self-define purposes, goals, self-programme and perform actions for achieving the self-defined goals, and has become increasingly independent of the environmental controls. Development of language skills in the brain has led to extensive verbal transcoding of perceptions, responses, actions, emotions, and experiences, as well as to the creation of new relationships at the conceptual and reality levels. The same neural functional systems monitor the process of creation of thoughts, the mental imageries, and their contents, which in turn has led to the emergence of awareness of the processes and contents of the transcoding. Experience is a product of sensory-motor events, emotions, their cognitive interpretations, and awareness. Despite the possibilities and the presence of erroneous as well as out of reality interpretations, experience offers the highest levels of personal contact with reality, which makes man crave and explore for it. The present book is thus a comprehensive study on brain-mind and it is hoped that it will prove useful and interesting to the students, researchers, and teachers of Neuropsychology. The detailed References included in the book will facilitate pursuing the studies further. Its language and approach to the subject matter is reader-friendly and easily comprehensible.